Journal Implications for the Decision of Sharia Economic Case Number 5K/Ag/2023 - Dhea Andini Nathania; Syifa Rahmalia Ridwani; Nurhasanah Nurhasanah; Udin Saripudin (Fakultas Studi Islam Universitas Islam Kalimantan Muhammad Arsyad Al Banjary, 2024)
Islamic economics is experiencing a rapid expansion, which may lead to inevitable conflicts. In Indonesia, the religious court is the authorized legal institution designated to resolve financial disputes related to Sharia law. Religious courts are authorized to settle financial disputes related to sharia in accordance with Law No. 7 of 1989 regarding Religious Courts and Law No. 3 as of 2006. The aim of this study is to gain a deeper understanding of the resolution of default disputes through the Supreme Court's decision titled